Fabrication of CuInSe2 Single Crystals from Melt Growth by Directional Freezing Method - Gaewdang, Ng.; Gaewdang, T. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Single crystals of the semiconducting compound CuInSe2 prepared from the melt by directional freezing method using the horizontal Bridgeman-Stockbarger traveling furnace and the temperature gradient freezing 45 degree tilt-furnace techniques. The experimental details and crystal morphology of the as-grown ingots obtained by both techniques were reported. X-ray powder diffraction patterns of the crushed crystals were carried out to determine the lattice parameters. The energy gap being 1.03 eV was evaluated, at room temperature, from the optical transmission spectrum. The conductivity types of the samples were either p-type or n-type with low resistivity values in the range 1.4 – 6.1 Ω-cm. The change in the electrical resistivity values of CuInSe2 was investigated by annealing at 100 – 600 °C in vacuum and in a slowly flow of pure nitrogen gas. At annealing temperature lower than 500 °C, the resistivity values of all samples were slightly changed. However, at annealing temperature higher than 500 °C, the p-type samples were changed to n-types ones except the n-type samples which remained the same conductivity type with slightly lower resistivity values. Keywords: CuInSe2, directional freezing method, electrical resistivity Corresponding author: E-mail: cast@kmitl.ac.th